Hegel y la participación política - Carla Cordua (Ideas y Valores)
This paper analyses Hegel's ideas concerning the forms of political •f. participation intne modem state.ltsubmíts that a fair account of Hegel's Eosition on democracy should consider aspects of his notion of political eedom, which have been usually neglected because of a few critical remarks ofthe philosopher. In particular, it should consider Hegel' s ideas on 1) modem freedom as Dabeisein; 2) modem citizenship as entailing Befriedigung. These two concepts are analyzed in their larger philosopnicaland political contents and their import for Hegel's thought